ЗАДАЧА О ДИФРАКЦИИ НЕСТАЦИОНАРНОЙ ПЛОСКОЙ ПОПЕРЕЧНОЙ ВОЛНЫ НА СФЕРИЧЕСКОМ ВКЛЮЧЕНИИ В УПРУГО-ПОРИСТОМ ПРОСТРАНСТВЕ - Мусурмонова, М.О. (SCIENCE and SOCIETY, 2022)
The paper considers the problem of diffraction of non-stationary transverse shear waves on a spherical inclusion in a porous-elastic space saturated with liquid. Numerical experiments were carried out, the results of which are presented in the form of graphs.
Keywords: transverse wave diffraction; spherical inclusion; Gegenbauer polynomials; Laplace transform; residues; porous-elastic medium